2016
DOI: 10.1101/gr.204255.116
|View full text |Cite
|
Sign up to set email alerts
|

The population genomics of rhesus macaques (Macaca mulatta) based on whole-genome sequences

Abstract: Rhesus macaques (Macaca mulatta) are the most widely used nonhuman primate in biomedical research, have the largest natural geographic distribution of any nonhuman primate, and have been the focus of much evolutionary and behavioral investigation. Consequently, rhesus macaques are one of the most thoroughly studied nonhuman primate species. However, little is known about genome-wide genetic variation in this species. A detailed understanding of extant genomic variation among rhesus macaques has implications fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
132
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 107 publications
(142 citation statements)
references
References 104 publications
(129 reference statements)
4
132
1
Order By: Relevance
“…The details of sequencing and single-nucleotide variants discovery for this population have previously been described 8 . The population-level VCF file for this study was examined for relevant variation in these two genes.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The details of sequencing and single-nucleotide variants discovery for this population have previously been described 8 . The population-level VCF file for this study was examined for relevant variation in these two genes.…”
Section: Methodsmentioning
confidence: 99%
“…2b). By contrast, analysis of the whole-genome sequences of 15 baboons and more than 130 rhesus macaques demonstrated that only the full-length ICAM-2 protein was found in all individuals (data not shown) 8 . The ICAM-2 deletion may be specific to C. atys , as it is not present in any other known primate sequences, including other natural SIV hosts, such as the African green monkey, drill and colobus monkey.…”
mentioning
confidence: 87%
See 1 more Smart Citation
“…Comparisons among individuals within the same species are used to understand the extent of variation within the species[54, 55]. The data for these analyses can be WGS or sample sequences like genotyping assays using chips designed for other species.…”
Section: Complementary Genomic Data That Synergistically Enhance Thementioning
confidence: 99%
“…Cornish et al highlight the importance of both the completeness of the reference assembly and accuracy of gene annotation for variant detection and functional prediction, demonstrating considerable improvement in the second generation MacaM genome over the earlier rheMac2 build [14]. Most recently, a study of 133 Rhesus macaques found approximately 2.5-fold higher overall nucleotide diversity and slightly elevated putative functional variation compared with humans [16]. Each of these studies identified examples of mutations predicted to adversely affect key proteins, which suggests that many naturally occurring disease models may be present in the population.…”
Section: Introductionmentioning
confidence: 99%